Cardiovascular Disease in Low and Middle Income Countries: Challenges and Solutions - Faiz Ullah; Atiq Ur Rehman; Khan, Rahim Dil; Orakzai, Hafeez; Ahmadyar; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Cardiovascular disease (CVD) stands among the principal reasons for death in low- and middle-income countries (LMICs) together with Pakistan. Medical areas with restricted healthcare access, limited resources, and elevated risk factor rates have caused cardiovascular disease to expand within such regions. Objective: An evaluation of CVD prevalence and treatment obstacles and results has been performed in a Pakistan-based tertiary care facility to identify improvement possibilities for LMICs cardiovascular care. Materials and Method: The study conducted at Department of Cardiology, Hayatabad Medical Complex Peshawar, Pakistan from September, 2024 to February, 2025 for the descriptive cross-sectional investigation. Patient interviews, clinical assessments, and medical record reviews gathered data from the sampled patients. Five hundred patients with diagnosed CVD were included in the study. Results: The most prevalent condition affecting patients was hypertension since it affected 60% of the population, while blood pressure control was adequate in only 30% of cases. Patients experienced difficulties obtaining needed medication treatment while dealing with multiple health conditions together with different controllable risk elements. Conclusion: This research shows that developing countries face serious obstacles in controlling CVD, which calls for better healthcare access together with improved management strategies and public health programs.